Using Anchor and Meaning Theory to Understand Human Suffering: Case Study of Conversation Text Luke 23:39-43 - Dhwi Waspodo, Katjuk; Sitepu , Edward; Triadi, Slamet; Situmorang, Lasmawati; Sihombing, Sihombing (International Journal Labs, 2025)
This study examines the narrative of human suffering as depicted in Luke 23:39-43 using Anchor and Meaning Theory. It focuses on the contrasting responses of two criminals crucified alongside Jesus, shedding light on their differing reactions to suffering. The first criminal represents a self-centered perspective, seeking immediate relief without recognizing Jesus' redemptive role, while the second criminal demonstrates faith, acceptance, and a transformative understanding of suffering. By exploring this dialogue, the study highlights the theological significance of suffering, emphasizing its potential for spiritual growth and redemption when anchored in faith. Employing an integrative causality approach, this research utilizes verbal analysis to uncover the cognitive and spiritual dimensions of the narrative. The findings contribute to pastoral care practices by offering insights into addressing human suffering with a focus on faith, redemption, and hope. This study seeks to provide a deeper understanding of the transformative power of suffering, encouraging individuals to embrace faith as a pathway to eternal salvation and joy.